Different contributions of ASIC channels 1a, 2, and 3 in gastrointestinal mechanosensory function. Issue 10 (29th June 2005) - Page, A J; Brierley, S M; Martin, C M; Price, M P; Symonds, E; Butler, R; Wemmie, J A; Blackshaw, L A
Abstract : Aims: Members of the acid sensing ion channel (ASIC) family are strong candidates as mechanical transducers in sensory function. The authors have shown that ASIC1a has no role in skin but a clear influence in gastrointestinal mechanotransduction. Here they investigate further ASIC1a in gut mechanoreceptors, and compare its influence with ASIC2 and ASIC3. Methods and results: Expression of ASIC1a, 2, and 3 mRNA was found in vagal (nodose) and dorsal root ganglia (DRG), and was lost in mice lacking the respective genes. Recordings of different classes of splanchnic colonic afferents and vagal gastro-oesophageal afferents revealed that disruption of ASIC1a increased the mechanical sensitivity of all afferents in both locations. Disruption of ASIC2 had varied effects: increased mechanosensitivity in gastro-oesophageal mucosal endings, decreases in gastro-oesophageal tension receptors, increases in colonic serosal endings, and no change in colonic mesenteric endings. In ASIC3-/- mice, all afferent classes had markedly reduced mechanosensitivity except gastro-oesophageal mucosal receptors. Observations of gastric emptying and faecal output confirmed that increases in mechanosensitivity translate to changes in digestive function in conscious animals. Conclusions: These data show that ASIC3 makes a critical positive contribution to mechanosensitivity in three out of four classes of visceral afferents. The presence of ASIC1a appears to provide an inhibitory contribution to the ion channel complex, whereas the role of ASIC2 differs widely across subclasses of afferents. These findings contrast sharply with the effects of ASIC1, 2, and 3 in skin, suggesting that targeting these subunits with pharmacological agents may have different and more pronounced effects on mechanosensitivity in the viscera.